Oxidation versus dioxygenation of catechol: the iron-bispidine system - Comba, Peter; Wadepohl, Hubert; Wunderlich, Steffen (European journal of inorganic chemistry, 2011)
The iron-bispidine-catalyzed oxidation and dioxygenation (catechol dioxygenase activity) [i.e., the oxidation of 3,5-di-tert-butylcatecholate (dbc2-) by [FeII(L)X2]n+ (L = 3,7-dimethyl-9-oxo-2,4-bis(2-pyridyl)-3,7-diazabicyclo[3.3.1]nonane-1,5-dicarboxylate methyl ester)] and air (O2) was studied experimentally and supported by the analysis of the X-ray crystal structure of [Fe(L·MeOH)(tcc)][B(Ph)4] with the deactivated tetrachlorocatecholate tcc2- and a DFT-based analysis. The [FeII(L)X2]n+/O2/dbc2- system catalyzes the intradiol cleavage of dbc2- but with a relatively low activity (5 % yield); most of the substrate is oxidized in a two-electron oxidation to the benzoquinone (dbq) product (48 % yield). The crystallographic and DFT-based theoretical analyses indicate that this is due to the high oxidation potential of the FeIII oxidant (fast and efficient electron transfer), that is, the oxidation to the benzoquinone side product is faster, and due to the bonding mode of the catecholate substrate to the FeIII oxidant, with little spin density transferred to the catecholate substrate.
First published: 31 October 2011
Gesehen am 07.04.2022